Effectiveness of a controlled release chlorhexidine chip (PerioColTM‑CG) as an adjunctive to scaling and root planing when compared to scaling and root planing alone in the treatment of chronic periodontitis: A comparative study - Kameswari Kondreddy; N Ambalavanan; T Ramakrishna; R Saravana Kumar (Wolters Kluwer Medknow Publications, 2012)
Aims and objectives: The aim of this study is to evaluate the effectiveness of a controlled-release chlorhexidine chip as an adjunctive therapy to scaling and root planing when compared with scaling and root planing alone in the treatment of chronic periodontitis. Materials and Methods: 20 patients with a total number of 40 posterior sites were selected. These sites were divided into two groups in a split mouth design,: Group A (control site) had 20 sites treated with scaling and root planing alone and Group B (test site) had 20 sites treated with scaling and root planing and PerioCol TM -CG. The clinical parameters (Plaque index, bleeding on probing, probing pocket depth, clinical attachment level) were recorded at baseline, 90 th and 180 th day for both the groups. Results: When both groups were compared the change in Plaque index was significantly higher in Group B when compared to Group A on the 90 th day and 180 th day. However, there was no statistically significant difference in the mean percentage of gingival bleeding sites between the two groups on the 90 th day, though Group B showed a statistically higher reduction in the mean percentage of gingival bleeding sites at the end of 180 th day. There was no statistically significant difference in probing pocket depth between the two groups on both 90 th and 180 th day. Gain in clinical attachment level was significantly higher in Group B when compared to Group A on the 90 th and 180 th day. Conclusion: From the results observed in this study, it can be concluded that the adjunctive use of PerioCol TM -CG was safe and provided significant improvement in both Plaque index and gingival bleeding index. It was also more favorable than scaling and root planing alone for gain in clinical attachment level.